49.5k views
5 votes
Can anyone help with problems 6 and 8 those are the only ones I cannot figure out

Can anyone help with problems 6 and 8 those are the only ones I cannot figure out-example-1
User Jack Wang
by
6.5k points

1 Answer

4 votes

Answer:


(f + g) (x)=x^2 +x +3


(f - g) (x)=-x^2 +5x +1

Explanation:

We have the following functions:


f(x)=3x +2\\ and
g(x) = x^2 -2x +1

First we find
(f + g) (x)

To find
(f + g) (x) we must add the function f(x) with the function g(x)


(f + g) (x)=3x +2 + x^2 -2x +1


(f + g) (x)=x^2 +x +3

Now we find
(f - g) (x)

To find
(f - g) (x) we must subtract the function f(x) with the function g(x)


(f - g) (x)=3x +2 - (x^2 -2x +1)


(f - g) (x)=3x +2 - x^2 +2x -1


(f - g) (x)=-x^2 +5x +1

User Mahi
by
6.2k points